Pengaruh Metode Pembelajaran Demonstrasi Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Fiqih Materi Shalat Jama`Qasar - Hartono, Rudi; Alwiyah, Alwiyah (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2024)
The objectives are (1) to find out how much influence the demonstration learning method has on the fiqh subject at MTs Miftahul Huda Cilegon (2) to find out how much influence the demonstration learning method has on student learning outcomes in the fiqh subject at MTs Miftahul Huda Cilegon. The research method used is a quantitative experiment with a Quasi Experiment type design with a Pre-test-Post-test non-equivalent control group design. The population of this research was class VII students at MTs Miftahul Huda Cilegon. The sampling technique used in this research was purposive sampling where class VII A had 23 students as the experimental class and class VII B had 23 students control class. The results of the t-test sample t-test calculation results show that there is a significant influence between variable 1.96 higher than the control class. It is known that the value of learning outcomes between experimental and control class students is obtained by T count > T table (2.781 > 1.682), so it can be concluded that Ho is rejected and Ha is accepted. Based on the research results, the demonstration method has an effect on learning outcomes in fiqh subjects in the experimental class, obtaining an average pre-test score of 66.09 and post-test of 85.43. It is known that the average increase in the experimental class is 19.34, so it can be concluded that there is a significant influence of the demonstration method on student learning outcomes in fiqh subjects in class VII MTs Miftahul Huda Cilegon. Keywords: Influence, Method, Demonstration and Learning Results